THE EFFECTIVENESS OF DISTANCE LEARNING IN COVID-19 PANDEMIC AT ELEMENTARY SCHOOL EDUCATION LEVELS IN SERANG DISTRICT - Nandang Faturohman; Elih Solihatulmilah (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
Education is the right of all citizens guaranteed by law, not least during the Covid-19 pandemic, students still have to get a proper education. This study aims to determine how the implementation of distance learning for elementary school students in Serang Regency. The focus of the research is to find out how distance learning policies issued by the central government are implemented by elementary schools. The research method used is a qualitative research method with the type of case study research, with data sources obtained from school principals, teachers and parents of students. Data collection techniques using non-participant observation, documentation and interviews. Data analysis includes data collection, data reduction, data presentation and conclusion drawing, then the data is triangulated. The results showed that each elementary school carried out distance learning using various approaches through tools that were also prepared by the schools themselves and prepared by the district government through the Education and Culture Office of Serang Regency, one of which was television media. The implementation of the PJJ experienced many obstacles in its implementation and was considered ineffective so that it had to be evaluated.